Gugatan Keperdataan Oleh Jaksa Pengacara Negara Sebagai Upaya Pengembalian Kerugian Keuangan Negara Karena Korupsi - Iwan Kurniawan; Riki Afrizal (Faculty of Law, Andalas University, 2021)
Stollen assets recovery is one of the main purpose of eradicating corruption policy in Indonesia. Private lawsuit is one of the mechanisms that can be used to achieve this purpose. This mechanism has been regulated in Law Number. 31 of 1999 as amended by Law Number. 20 of 2001 Concerning the Eradication of Crimes of Corruption. This article analyses the extent to which private lawsuits mechanism in that Law can normatively accommodate the efforts to recover state financial losses due to corruption and the problems faced by State Attorneys in implementing these rules. This study uses both normative and empirical legal research methods. Primary data in this research was carried out by purposive sampling method in several District Attorney offices in West Sumatra. From what has been done, it can be said that the rules regarding private lawsuits in Law no. 31 of 1999 and Law No. 20 of 2001 concerning The Eradication of Crime of Corruption has opened a fairly flexible space for state attorneys to submit private action to recover state financial losses. However, the space provided by these laws and regulations has not been fully utilized by the Attorney General's Office, especially the District Attorney's Office in West Sumatra. There are several problems, both juridical and non-juridical in nature, such as: the problem of proof in the civil case, the misunderstanding of the attorney officer about the rules of private lawsuits in that Law, the problem of tracking assets, and the problem concerning the benefits or profits. In fact, the profits obtained from this private lawsuit do not have a significant impact on efforts to recover state losses.